Effectiveness of Implementing a Reminder Control Information System Using the SKEDit Program for Diarrhea Patients: Efektifitas Penerapan Sistem Informasi Reminder Control Menggunakan Program SKEDit Pada Pasien Diare - Muhamad Hasan Basri; Agus Meriroja; Muhamad Zulfatul A’la; Dodi Wijaya (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Diarrhea is one of the main causes of death in the world. Environmental cleanliness, sanitation and access to clean water are still factors that trigger diarrhea, especially in developing countries such as Indonesia. Diarrhea can attack anyone at any time, both adults and children. This Community Service aims to determine the effectiveness of using the control reminder information system for diarrhea patients in increasing repeat visits at the Mayang Community Health Center. The implementation method is carried out by providing health education by providing information about diarrhea through posters, sending health education videos and Control message reminders using the SKEDit Application Program. Evaluation before health education was carried out using SKEDit, customer satisfaction was 67.8% and after health education was carried out using SKEDit, it was 80.1%. Meanwhile, the rate of repeat visits for diarrhea patients after receiving a control reminder increased by 70%. Based on the results of observations, it shows that this Community Service activity is able to increase customer satisfaction and increase repeat visits of diarrhea patients at the Mayang Community Health Center.